Visibilidade e impacto da literatura cinzenta produzida na Universidade Federal de Minas Gerais: os impactos acadêmico e social das teses e dissertações - Belkiz Inez Rezende Costa (2019)
This research aims to analyze the academic and social impacts of the theses and dissertations of the Graduate Programs in Infectious Diseases and Tropical Medicine, Computer Science and Information Science, Federal University of Minas Gerais, defended between 2002 and 2018 and made available. in the Digital Library of Theses and Dissertations of this institution. The theoretical foundation includes authors and theories related to the themes of scientific communication; formal and informal channels; grey literature; theses and dissertations; digital libraries of theses and dissertations; citation analysis and academic impact; and altitude and social impact. The research is configured as descriptive and exploratory, with quantitative and qualitative approach and use of bibliometric and altmetric methods. The sample consisted of 1,383 documents, 367 theses and 1,016 dissertations. The methodological procedures were divided into three stages. In the first stage, we consulted the UFMG Digital Library of Theses and Dissertations, to list theses and dissertations, by selected graduate program. In the second stage, Google Scholar was used to measure the academic impact. Through manual collection, we identified the indexed theses and dissertations in the Google Scholar database, the citations, the types of documents that cited these documents and the most cited themes. In the third stage, the Mendeley reference manager was used to measure social impact. For the data collection procedure, the Webometric Analyst software was used to identify Mendeley's theses and dissertations, to quantify readers by thesis or dissertation, by nationality, occupational profile and area of knowledge. For the treatment of the data and elaboration of graphs and tables, it was resorted to the program Microsoft® Excel®. The results obtained for the Graduate Program in Computer Science indicated that the 567 dissertations received a total of 372 citations, and the 149 theses received a total of 205 citations in Google Scholar. We identified 15 dissertations and 4 theses marked in Mendeley that accumulated a total of 156 readers for the dissertations and 16 readers for the theses. The results for the Graduate Program in Infectious Diseases and Tropical Medicine indicated that the 153 dissertations received a total of 145 citations, and the 68 theses received a total of 55 citations on Google Scholar. Two identified dissertations were identified in Mendeley. The dissertations accumulated a total of 18 readers and the theses were not identified in the Mendeley collection. Regarding the Graduate Program in Information Science, the results showed that 296 dissertations received a total of 899 citations and the 150 theses received 1,013 citations in Google Scholar. We identified 60 dissertations and 40 theses marked in Mendeley. The dissertations accumulated a total of 295 readers and the theses, 410 readers in Mendeley. The main findings were that: a large number of theses and dissertations were not present in the digital library and were not indexed by Google Scholar; Information Science theses and dissertations had a significant academic impact; The results show that in scientific production there are variations in the typology of the source cited; citations were present in international theses and dissertations; There was a diversity of subjects addressed in the theses and dissertations of the three areas researched, and some themes were recurring. Regarding the Mendeley markings, a large number of works related to journal and event articles, derived from the researched theses and dissertations, were found. Regarding the number of readers, the research pointed out that the Information Science Program obtained better results compared to the other areas analyzed. Regarding nationality, it was noticed that the readers are mostly Brazilian, with a timid presence of readers of foreign nationalities. Graduate Students (Master and Doctorate) was the profile with the largest number of readers, followed by Undergraduate students. Regarding the areas of knowledge, readers declared themselves to be from the same areas of theses and dissertations or related areas. It was concluded that it was possible to analyze both the academic and social impact of the theses and dissertations of the Graduate Programs selected and available in the UFMG BDTD. The use of Google Scholar and Mendeley allowed to point the access and visibility of theses and dissertations of this University. Although open access has made theses and dissertations more accessible, the use of these documents is still incipient in relation to citation behavior in all three areas.